Peace with Nature: Engagement of CGIAR Livestock and Climate Initiative in the Convention for Biological Diversity COP16 - Nanteza, P.; Flintan, Fiona E.; Ferrari, M. (CGIAR System Organization, 2024)
"Under the theme Peace With Nature, this was the first Biodiversity COP since the adoption of the Kunming-Montreal Global Biodiversity Framework at COP 15 in December 2022 in Montreal, Canada. Parties to the Convention were expected to show the alignment of their National Biodiversity Strategies and Action Plans (NBSAPs) with the Framework. It was expected that COP16 would produce a monitoring framework and advance resource mobilization for the Global Biodiversity Framework as well as finalize and operationalize the multilateral mechanism on the fair and equitable sharing of benefits from the use of digital sequence information on genetic resources. This report summarizes the activities in and contributions of the CGIAR Research Initiative on Livestock and Climate to the CBD COP16. Members of the Initiative participated in discussions on peace with nature, improved natural resource management, protection of biological diversity and the critical role of multifunctional landscapes in biodiversity conservation and sustainable development. "